Application Of Rms Model (Reading, Mind Mapping and Sharing) To Improve Student's High Level of Thinking Ability to Learning Physics at SMA Negeri 1 Sigli - Ilyas Ilyas; Muhammad Saiful; Amirzan Amirzan; Mariati Mariati; Pocut Nabila Maora (Budapest International Research and Critics University, 2022)
This study aims to determine the effectiveness of the RMS (Reading, Mind Mapping, and Sharing) model on students' higher order thinking skills. This type of research is a quasi experimental. The population in this study were students of class XI MIA program at SMA Negeri 1 Sigli, the sampling technique used was purposive sampling. Class XI MIA 2 as the experimental class and class XI MIA 3 as the control class, this research was conducted with the material temperature and heat. The instrument given to measure students' higher-order thinking skills was tested in the form of an essay totaling 8 questions. The independent t-test was used to determine the difference in students' higher-order thinking skills between using the RMS (Reading, Mind Mapping, and Sharing) model with the conventional model. From the results of the research analysis, it is stated that there are differences in higher order thinking skills between students who are treated using the RMS (Reading, Mind Mapping, and Sharing) model and students who are not given treatment or use conventional models. This is evident from the obtained sig value of 0.000, which means the sig value <0.05, it can be concluded that learning Physics using the RMS (Reading, Mind Mapping, and Sharing) model is quite effective on students' higher-order thinking skills. The effectiveness of the RMS model can also be seen in the effect size test which obtains a value of 2.07 which is included in the high category. It can be interpreted that the RMS (Reading, Mind Mapping, and Sharing) model has a high enough effect on the high-level thinking skills of class XI students of the MIA program at SMA Negeri 1 Sigli in the field of physics subjects.